Analisis Pengukuran Beban Kerja Mental Pekerja Produksi CV. Hikmah Jaya Garment Menggunakan Metode NASA-TLX dan RSME - Maulida Dewi Amanda; Isna Nugraha (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Hikmah Jaya Garment is a company that produces various clothing equipment and apparel manufacturing. With the number of production requests that continue to increase every time as well as the application of the make-to-order system which causes an uncertain production schedule, it causes the emergence of its own work demands for workers. These conditions can affect the quality of the production results they are working on, so this study aims to analyze the mental workload experienced by employees at CV. Hikmah Jaya Garment is a reference for providing improvement solutions to increase work productivity. This research uses the National Aeronautics and Space Administration Task Load Index (NASA-TLX) and Rating Scale Mental Effort (RSME) methods through a questionnaire containing factors or indicators of mental workload to workers. Based on the results of calculations and analysis, the average NASA-TLX score is 74.9% and the average RSME score is 83.1%, which means that the mental workload experienced by workers is in a high category with the amount of effort expended included in a large enough category. These high results cause less than optimal worker productivity so there are several recommendations for improvement in the aspects of workload indicators. Keywords: Mental Workload, NASA-TLX, Production, RSME, 5S